Multifiring endoclip conceptual design using cad approach - Siregar, I; Adenan, MS; Ariffin, AC; Saedon, JB; Asro, H (IOP Publishing Ltd, 2024)
The endoclip design that will be done is by designing cartridge components that have several clips. In essence, endoclip is a mechanical device in the world of health, especially for endoscopic activities, which are also used for the process of hemostasis and also non-hemostatic applications. This study describes the relationship between end-time end-endoscopic problems during gastrointestinal standards. Currently, market-available endoclips only focus on single-firing, where the process is carried out one by one. The use of Endoclip at this time is very difficult because of the repetition of the clip loading process to the applicator. Therefore, the purpose of this research is to design cartridges which consist of several clips for endoclip and allow for mechanical movements. The method of selecting the appropriate and important part of the tip which is the most important way to solve the problem and the design and process of the simulation is done using CATIA V5 software. The aim of this study was achieved by increasing the critical part of the catheter by replacing it with a cartridge design that contained several clips that allowed the clipping process to be multi-firing, not one-shot and also by simulating the mechanism.